2014
DOI: 10.1007/s00264-014-2582-9
|View full text |Cite
|
Sign up to set email alerts
|

Coating with a novel gentamicinpalmitate formulation prevents implant-associated osteomyelitis induced by methicillin-susceptible Staphylococcus aureus in a rat model

Abstract: Gentamicin palmitate appears to be a viable coating for the prevention of implant-associated infections. These findings will have to be confirmed in larger animal models as well as in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Representative animal models of osteomyelitis are valuable tools since they allow diagnostic and therapeutic research to keep moving forward [11]. Experimental handling of such animal models of infection diseases usually involves microbiological evaluation of the infected organ and searching for macro or micro changes in it such as bacterial colonization as well as morphological and histopathological changes [12][13][14][15]. The evaluation of these parameters is related, in a non negotiable way, to animal euthanasia which avoids the follow up of the same animal during the development of the disease or even worse, the follow up of a treatment using the same animal.…”
Section: Discussionmentioning
confidence: 99%
“…Representative animal models of osteomyelitis are valuable tools since they allow diagnostic and therapeutic research to keep moving forward [11]. Experimental handling of such animal models of infection diseases usually involves microbiological evaluation of the infected organ and searching for macro or micro changes in it such as bacterial colonization as well as morphological and histopathological changes [12][13][14][15]. The evaluation of these parameters is related, in a non negotiable way, to animal euthanasia which avoids the follow up of the same animal during the development of the disease or even worse, the follow up of a treatment using the same animal.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the drug, antibiotic-coated implants generally showed a 0.3–4.5 log-reduction of colonized bacteria (MSSA or MRSA) in bone and 0.35–4.5 log-reduction on implants in comparison to a non-coated control. 204,207,211,213,217219 Diefenbeck et al demonstrated that plasma chemically oxidized titanium rods coated with gentamicin and gentamicin+tannic acid showed 100% and 90% protection in a rat tibia infection model. 214 Additionally, Metsemakers et al demonstrated highly favorable results in a rabbit infection model, where doxycycline-coated intramedullary nails had 100% protection against MSSA (JAR060131; doxycycline-susceptible clinical isolate) and 43% protection against MRSA (LUH15101; doxycycline-resistant clinical isolate).…”
Section: Novel Antibiotic Therapies To Combat Osteomyelitismentioning
confidence: 99%
“…Rabbits have traditionally been preferred models for joint arthroplasty, however rat models are increasingly being developed . Due to their smaller size, rodents are rarely suitable for looking at implant biomechanics, but can be very effective for examining the osseointegration of implants with novel biomaterial surfaces, in conjunction with new biological agents, and/or in the presence of infection …”
Section: Orthopedic and Bone Tissue Engineering Modelsmentioning
confidence: 99%